INTEGRITY STUDY AND ANALYSIS FOR REPAIR METHODS OF DEGRADED GAS PIPELINE - INDRAWAN (NIM : 13106068); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, LAVENDO
At the time of operation, pipeline will come into contact with working fluid and the surrounding environment. Surrounding environment and this fluid contains chemical elements that are corrosive. This can cause pipeline walls corroded and causing damage to the pipeline. Pipeline degraded or thinning of the pipe wall will experience a decrease in strength and in disrepair. Therefore we need an integrated analysis starting from identifying the threat, risk assessment, inspection, repair, and mitigation. The series of activities is referred to as pipeline integrity set forth in ASME B31.8s. In this final study, conducted studies to analyze the state of pipeline integrity that are running. The study includes the determination of the critical point in the pipeline using a program based on the ASME B31.G aids, recommendations for improvement to be done, and level 3 analyze using the finite element method. As a case study, the analysis is done on the gas transmission pipeline tegal gede – bitung. From the results of the determination of the critical point for the next 10 years, gained 18 points to the critical point A-140 (KM 27.4 of the pig launcher) in the first year. Point - the point is already past the limit allowed by the depth of defects ASME code B31.G. Of the 18 points, the recommended repair methods and sleeve patch. Both methods of repair to meet the criteria specified in ASME B31.8. Analysis 3 shows the voltage levels that occur in the corroded pipe wall before the repair is in critical condition, that is 257.97 MPa (81% SMYS). Meanwhile, if repaired using a patch with a minimum thickness of 1.5 in. or sleeve of 1 in, the stress experienced by the corroded wall fell to 113.80 MPa (35% SMYS) if the repair method used is a patch, and 62.59 Mpa (19% SMYS) if using a sleeve. To ensure safety while improving the pipe, the maximum allowable pressure must be reduced by 60%. This can be seen from the calculation of design pressure based on ASME B31.8. The design pressure will determine how the maximum pressure allowed. it’s 2.59 MPa (52% MAOP) for the method of patching and 2.32 MPa (60%) for the sleeve method.